Current epidemiologic features and health dynamics of ESBL-producing Escherichia coli in China - Sayyed Salman; Zeeshan Umar; Yonghong Xiao (Biosafety and Health, 2024)
Extended-spectrum β-lactamase (ESBL)-producing Escherichia coli (E. coli) are widespread in China, with occurrences documented in humans, animals, and the environment. The dissemination of ESBL-producing E. coli is likely facilitated by the widespread use of antibiotics in human and animal agriculture, the presence of antibiotic-resistant bacteria (ARBs) in animal feces, and close human-animal interactions. Plasmids, particularly those belonging to incompatibility (Inc) group, such as IncF, IncI, and IncH families, play a vital role in facilitating the horizontal gene transfer of ESBL genes across various sectors, from humans to animals and the environment. IS26 and IS1 elements also significantly influences the mobilization and evolution of antibiotic-resistance genes (ARGs), contributing to the spread of ESBL-producing E. coli. blaCTX-M−14, blaCTX-15, and blaCTX-M−55 are prevalent in ESBL-producing E. coli across the three domains and are often found in conjunction with other ARGs. Considering these challenges, it is imperative to take proactive measures to prevent the further spread of ARBs. This includes the judicious and responsible use of antibiotics and efforts to minimize contact with animal feces. Sector-specific strategies should be developed to effectively educate and engage relevant personnel in tackling this multifaceted problem. These efforts are vital to combat the dissemination of ESBL-producing E. coli and preserve public health.